Corpus-Based study: exploring the frequency of ‘Nouns’ used in poetry written by UiTM undergraduates - Ismail Shauki, Nur Baiti; Kaur, Manvender (UMK Press, 2018)
This study aims to investigate the frequency level of ‘nouns’ used in poems written by the undergraduates of Universiti Teknologi MARA Kampus Machang based on Paul Nation’s headword list. The importance of knowing the frequency will determine teacher’s priority in teaching vocabulary. The effect of teacher’s implementation of standard nouns in classroom should reflect in the target behavior of the learner as they utilize the word in writing and mostly in communicating. The methodology used in this mini-scaled investigation of the written communication is the Computer-Assisted Corpus Analysis (CACA). Ten poems written by ten undergraduate students were collected and analysed by Tagger C5 tagset to identify the ‘nouns’ and separate it from other content words. Subsequently, ‘nouns’ frequencies were calculated by using AntConc software in order to determine the type of noun that most frequently occurred in the student’s writing. The list of 107 words was then compared to Paul Nation’s English Vocabulary Profile (EVP) program of academic vocabulary to determine the level of vocabulary that the students possessed. In the discussion section, the result of the frequency is analysed to determine whether the level is at par with the standard vocabulary knowledge or below. Although the concordance overall results show that ‘nouns’ was the most frequent used word in the poems.